Gambaran Cakupan Imunisasi Inactivated Polio Vaccine (IPV) Berdasarkan Faktor Indeks Dan Kipi Bagi Bayi Dan Balita Di Upt Puskesmas Pagarsih Kota Bandung - Marjani Khoirunnisa; Cindy Asella Sari (Jurnal Ilmiah JKA (Jurnal Kesehatan Aeromedika), 2018)
Immunization is the immune system that can prevent the disease one of them polio. Polio is a disease caused by a virus that can cause paralysis. Polio eradication is a change in the use of OPV to lPV because OPV is a virus that is attenuated by way of oral whereas IPV virus is switched off by injection. The official incidence of polio cases in the world is 350,000 cases. The coverage of Inactivated Polio Vaccine (IPV) PIN in 2017 in Indonesia should reach 75%, unfortunately this coverage still has not met the target due to many factors that affect the index and KIPI factors. The aim of this research is to find out IPV Immunization Coverage Scenario based on Index Factor and KIPI for Infants and Toddlers at UPT Puskesmas Pagarsih Bandung period January-April 2017. Type of descriptive research, univariate analysis, population 67 people, sample 67 respondents, and determined by total sampling. Results of coverage of 26.5% IPV immunization, 1.9 vial usage index, and KIPI have 5 (7.5%) infants and toddlers with local reactions. Suggestion for service institution as health worker is expected to do management in effort of prevention of polio disease for infant and toddler using immunization socialization.